2005
DOI: 10.1007/s10802-005-3567-3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of First-Grade “Friendship Group” Experiences on Child Social Outcomes in the Fast Track Program

Abstract: Many interventions for children's behavior problems successfully utilize a group format for social skills training, providing opportunities for practice and performance feedback from peers. Recent studies however, suggest that grouping aggressive children together may reduce intervention effectiveness or even increase risk. The present study examined the relative impact of children's own behavior and their experiences with peers in the first-grade "friendship groups" of Fast Track, a multi-component preventive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 47 publications
0
29
1
Order By: Relevance
“…Discrepancies between one's self-perceptions and one's perceptions of friends are examined in relation to aggression and rejection (Prinstein & Wang, 2005) and change processes were observed in "friendship" intervention groups (Lavallee et al, 2005). But the interpersonal relationships existing between influence sources and the individuals being influenced is not dealt with in these reports.…”
Section: The Relationship Between Influencer and Influencedmentioning
confidence: 99%
“…Discrepancies between one's self-perceptions and one's perceptions of friends are examined in relation to aggression and rejection (Prinstein & Wang, 2005) and change processes were observed in "friendship" intervention groups (Lavallee et al, 2005). But the interpersonal relationships existing between influence sources and the individuals being influenced is not dealt with in these reports.…”
Section: The Relationship Between Influencer and Influencedmentioning
confidence: 99%
“…Lavallee and colleagues examined the extent to which individual outcomes amongst participants of the friendship groups were influenced by individual and group characteristics. Overall, they showed that the Friendship Groups achieved high levels of positive in-session behavior and that peer-escalation was typically well controlled (Lavallee et al 2005). However, consistent with the deviancy-training hypothesis, peer reinforcement of disruptive behavior was associated with less desirable outcomes in some groups.…”
Section: Group-based Programs With Targeted Populationsmentioning
confidence: 83%
“…More evidence shedding light on the social dynamics involved in group interventions comes from the study by Lavallee et al (2005) on the Friendship Groups' component of the Fast Track prevention project. This intervention involved 55 groups of 5-6 children attending first grade of primary school and being identified as belonging to the 10-15% children with the highest scores of aggressive and disruptive behavior, according to teacher and parent assessments.…”
Section: Group-based Programs With Targeted Populationsmentioning
confidence: 99%
“…One of our main goals was to address measurement challenges that have hampered empirical investigations of deviancy training in residential treatment (Dishion et al 1996). Research using counselor, parent, and self-reports (Lavallee et al 2005;Mager et al 2005) in communitybased treatment has been promising, but residential treatment creates special challenges, including numerous peer interactions that could undermine prosocial treatment goals and encourage deviance throughout the therapeutic day rather than just in a therapy group. This led us to test a different approach that asked youth to nominate peers who engaged in rule-breaking talk and showed interest in and encouragement of rule-breaking in others.…”
Section: Discussionmentioning
confidence: 99%
“…Because peer nominations are aggregated, reliable and valid indices can be obtained using relatively few items (Weiss et al 2002). Other clinical assessments of deviancy training have relied on 1-2 items, aggregated over two time points (Lavallee et al 2005) or two raters, such as clinician/observer or parent/youth to improve reliability (Leve and Chamberlain 2005;Mager et al 2005). One downside of our approach is that we were unable to measure dyadic reinforcement directly.…”
Section: Rule-breaking By Individual Dtmentioning
confidence: 99%